Episentrum Baru Konsumsi Rokok: Siapa Tertinggi dan Siapa Tercepat di Indonesia, 2020–2024? - Agistin, Wina Anggi (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2025)
Cigarette consumption in Indonesia remains persistently high and constitutes a major determinant of non-communicable disease burden, preventable mortality, and socio-economic losses. The core problem lies in the uneven effectiveness of tobacco control policies across regions, while most previous studies remain sectoral and cross-sectional, limiting their ability to capture spatial variability and temporal dynamics comprehensively. Addressing this gap, this study aims to analyze the provincial distribution of cigarette consumption and its growth dynamics during 2020–2024. The research is grounded in the Social Determinants of Health and Political Economy of Tobacco (grand theory), consumer behavior and health risk theories (middle-range), and spatial distribution epidemiology with longitudinal trend analysis (applied theory). A quantitative descriptive approach was employed using regional distribution and temporal dynamics analysis based on secondary data from the National Socio-Economic Survey (Susenas). Analytical techniques included comparative tabulation and Compound Annual Growth Rate (CAGR) estimation. Findings reveal a moderate national increase from 28.69% (2020) to 28.99% (2024), masking substantial provincial disparities. High-consumption clusters are concentrated in Lampung, Bengkulu, West Java, and West Nusa Tenggara, whereas Bali, Jakarta, and Papua represent low clusters. Temporally, several provinces exhibit accelerated growth while others show sharp contractions. The integrated spatial-temporal findings confirm that Indonesia’s tobacco consumption landscape is geographically dynamic, implying that intervention priorities should consider both prevalence levels and growth rates. The study recommends regionally differentiated tobacco control strategies integrating fiscal instruments, market regulation, and social interventions.